Accountability for Food Poisoning Cases in the Free Nutrition Program in Islamic Law (Analysis of Diyat and Ta'zir) - Muh Tabran (Siyasah Wa Qanuniyah, 2026)
The concept of accountability in Islamic criminal law, Diyat and Ta'zir, in cases of food poisoning that can results in death and physical and sensory damage, provides a clear picture of the concept of punishment in Islam with the aim of protecting life and achieving the objectives of the free nutritious meal program (MBG). This study uses a qualitative approach with library research, which is descriptive in nature and normative in terms of Sharia law. Data collection used the Publish or Perish database on Google Scholar. Primary data consisted of articles indexed by Scopus and Sinta, as well as laws. Secondary data consisted of news reports. The data analysis method used was Miles Huberman and Saldana, reduction, display, and presentation. The results of the study show that the responsibility for accidental poisoning cases includes Diyat Mukhaffah, which is paid with 100 camels, and intentional poisoning is punished with Diyat Mughallazah, which is paid with 100 camels with aggravation if forgiven. Ta'zir for unintentional poisoning is punished with a fine and imprisonment under Law No. 18 of 2012 and Article 359 of the Criminal Procedure Code. Ta'zir for intentional poisoning is punished with the penalty for premeditated murder under Article 340 of the Criminal Procedure Code, or life imprisonment or 20 years' imprisonment. The conclusion of this study is that liability for cases of poisoning from free nutritious food, Diyat and Ta'zir offer solutions and lessons or deterrent effects on perpetrators, so that this program can run optimally by paying attention to food safety and ensuring the lives of the Indonesian people in order to achieve nutritional fulfillment.